Readliness Level Of Mobile-Based Mini English-Indonesia-Korean Dictionary Application Implementation In Improving The Tourism Sector - Kusuma Dewi, Ayu Aprilyana; Indrawan, I Putu Eka (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2023)
The tourism sector has the advantage that it is currently undergoing continuous expansion and diversification compared to the manufacturing sector. Current tourism development in various regions offers innovative services through the application of information and communication technology. Currently, the application of mini dictionary applications is more widely applied in city tourism areas that have complete basic infrastructure, adequate availability of information and communication technology and a comprehensive service system. In the tourism sector in Indonesia has considerable potential and attractiveness in the natural and cultural tourism sector, in the development of tourism the central government through The Ministry of Tourism and Creative Economy/Tourism and Creative Economy Agency in each province has the aim of increasing the number of visits and services. This research will examine each tourist attraction, which in its development has developed as an urban area with the availability of supporting tourism facilities / infrastructure that has been fulfilled. The purpose of this study is to identify the level of readiness of tourist attractions in implementing mini dictionary applications in terms of the availability and quality of basic infrastructure services and ICT and tourist support facilities. This research uses the waterfall process method used to describe the research approach to the analysis process. The results of the analysis show that the level of readiness of the application of mini dictionaries at tourist attractions is stated to be against ready. The readiness of the application of the mini dictionary in terms of the availability and quality of basic infrastructure services and ICT and tourist support, based on the results of a review of all components in its application that can be reviewed from infrastructure, facilities and service systems shows that almost all tourist attractions have shown readiness in basic infrastructure and for ICT infrastructure and tourist support facilities are still in a somewhat ready position. This is due to the inadequate quantity and also ICT that has not been applied in tourism management.